STAFF MONITORING, DEVELOPMENT, PERFORMANCE APPRAISAL, REWARD, AND DISCIPLINARY PRACTICES JOINT LINK WITH JOB PRODUCTIVITY OF BUSINESS EDUCATORS IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The study focused on monitoring, staff development, staff performance appraisal, staff reward, and staff disciplinary practices adopted by administrators and business educators’ job productivity in tertiary institutions in Anambra state. One research question guided the study, and one null hypothesis which were tested at 0.05 level of significance. Correlational research design guided the study. The study was carried out in four tertiary institutions in Anambra State. Population of the study was 122 which comprised of 118 business educators and 4 administrators from tertiary institutions in Anambra State. Census sampling technique was adopted because the sampling is manageable. A structured 5-point questionnaire containing 50 items in 5 clusters was used for answering research questions on human resource management practices while a 10 items questionnaire covered the business educators’ job productivity. The questionnaire was validated by experts in the field while Cronbach Alpha was used to test the reliability of the instrument resulting to coefficient alpha greater than 0.70. The data generated from the study were analyzed using inferential statistics of Pearson product moment correlation co-efficient and multiple linear regression. The Pearson product moment correlation was used to answer the research question while multiple regression was used to test the null hypothesis 0.05 level of significance. The findings from the study revealed that human resource practices such as monitoring, staff development, staff performance appraisal, staff reward and staff disciplinary practices do not influence business educators’ job productivity in tertiary institutions in Anambra State. Consequently, the study recommended that administrators should continuously evaluate the effectiveness of human resource management practices and make adjustments based on feedback and outcomes from business educators.
Keywords: Human resource management practices; job productivity